2018
DOI: 10.1016/j.fishres.2017.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Hydroacoustics to examine fish association with shallow offshore habitats in the Arabian Gulf

Abstract: In order to implement spatial fisheries management in the Arabian Gulf, a better understanding of the distribution of fish in relation to benthic habitats is required. To facilitate this, hydroacoustic fish surveys were conducted over oyster bed/reef ("shallow") and surrounding soft sediment ("deep") habitats in the offshore central Gulf, within Qatari waters. Transects at 'shallow' sites had significantly higher mean fish density and biomass. Mean target strength of individual fish was also significantly high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 64 publications
(62 reference statements)
0
7
0
Order By: Relevance
“…The majority of non-market species are integral components in maintaining the existence of commercial species firstly as part of a trophic chain and secondly by providing structural habitat (Cranfield et al, 2003). The importance of maintaining a complex benthic topography in the region was established during recent hydroacoustic surveys within fished hairãt which showed that the highest densities of high value commercial fish species were associated with the most complex topographical habitats, whereas sites with a featureless profile had low-density assemblages of low value fish (Egerton et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The majority of non-market species are integral components in maintaining the existence of commercial species firstly as part of a trophic chain and secondly by providing structural habitat (Cranfield et al, 2003). The importance of maintaining a complex benthic topography in the region was established during recent hydroacoustic surveys within fished hairãt which showed that the highest densities of high value commercial fish species were associated with the most complex topographical habitats, whereas sites with a featureless profile had low-density assemblages of low value fish (Egerton et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Intrinsic fish-habitat associations between the Qatari hairãt and a number of commercially important demersal species were recently confirmed in hydroacoustic surveys of sites which were once renowned as prolific during the pearl fishing epoch (Egerton et al, 2018) and wider habitat surveys (Walton et al 2017). Planning future management strategies for fish stocks should recognize the essential habitual niche of these fish, as many spend their entire life cycle associated with specific reefs (Egerton et al, 2018) while the Gargoor fleets consistently target traditional hairãt sites (Stamatopoulos and Abdallah, 2016).…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…Newman et al, (2015) showed that the more complex a reef surface the greater the associated richness. Egerton et al, (2018) Osmundea pinnatifida which contributed 47% of the differences between the oysters.…”
Section: Accepted Manuscriptmentioning
confidence: 99%